BIMBINGAN ROHANI DAN PEMBAGIAN SEMBAKO SEBAGAI MODEL PELAYANAN HOLISTIK BAGI MASYARAKAT PEDALAMAN KAMPUNG BOTAWA, KABUPATEN WAROPEN, PAPUA - Ronal Riki Lego; Ferry Simanjuntak (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2026)
Botawa Village is a remote village in Risei Sayati District, Waropen Regency, Papua, that is geographically difficult to access and far from public services and churches. This condition causes some residents to rarely attend worship, experience structural poverty, and live in substandard housing. This community service activity is aimed at providing holistic ministry that combines spiritual guidance with the distribution of basic food packages (sembako) for the people of Botawa Village. The method used was a field survey, literature study, and a participatory approach involving the Suara Kebenaran GBI COP community team. The activity was carried out in four stages: preparation, coordination with community leaders, implementation of spiritual guidance and food distribution, and evaluation. The results show increased resident participation in worship, improved understanding of biblical teaching, and personal testimonies of spiritual restoration. The distribution of basic food packages also helped meet the short-term food needs of underprivileged families. This activity demonstrates that ministry integrating spiritual and physical dimensions reaches remote communities more effectively than ministry addressing only one dimension. It is recommended that similar activities be conducted periodically and supported by more systematic needs mapping.